2022
DOI: 10.3390/plants11111445
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Pathogenicity of Paramyrothecium Species Associated with Leaf Spot Disease in Northern Thailand

Abstract: Species of Paramyrothecium that are reported as plant pathogens and cause leaf spot or leaf blight have been reported on many commercial crops worldwide. In 2019, during a survey of fungi causing leaf spots on plants in Chiang Mai and Mae Hong Son provinces, northern Thailand, 16 isolates from 14 host species across nine plant families were collected. A new species Paramyrothecium vignicola sp. nov. was identified based on morphology and concatenated (ITS, cmdA, rpb2, and tub2) phylogeny. Further, P. breviseta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…(RLCS10, De Mers, 2022; Htun et al, 2022;Martinko et al, 2022;Xu et al, 2022), RLCS22-Paraphoma chrysanthemicola (Wang et al, 2022), and RLCS23-Paramyrothecium sp. (Haudenshield et al, 2018;Pinruan et al, 2022;Withee et al, 2022),. These isolates were more tolerant to the sub-lethal concentrations of either prothioconazole or isopyrazam used in this study.…”
Section: Implication Of Differential Sensitivity On Potential Soil-bo...mentioning
confidence: 99%
“…(RLCS10, De Mers, 2022; Htun et al, 2022;Martinko et al, 2022;Xu et al, 2022), RLCS22-Paraphoma chrysanthemicola (Wang et al, 2022), and RLCS23-Paramyrothecium sp. (Haudenshield et al, 2018;Pinruan et al, 2022;Withee et al, 2022),. These isolates were more tolerant to the sub-lethal concentrations of either prothioconazole or isopyrazam used in this study.…”
Section: Implication Of Differential Sensitivity On Potential Soil-bo...mentioning
confidence: 99%
“…Recent examples are: on eggplant in the Philippines (Aumentado and Balendres 2022), on watermelon in Mexico (Cruz-Lachica et al 2021), and tomato in China (Huo et al 2022). Besides that, cross-inoculations of P. foliicola have indicated that this species is a polyphagous fungal pathogen capable of infecting unrelated crop plants such as lettuce, coffee, and soybean (Matić et al 2019;Withee et al 2022). Paramyrothecium foliicola was originally isolated from an unidentified rotten leaf in Brazil (Lombard et al 2016).…”
mentioning
confidence: 99%
“…In the research paper of Withee et al [ 14 ], 16 isolates of Paramyrothecium spp. retrieved from 14 host species across nine plant families are collected and identified.…”
mentioning
confidence: 99%